1993
DOI: 10.1002/1097-0142(19930601)71:11<3514::aid-cncr2820711109>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Nonepiphyseal giant cell tumor of the long bones. Clinical, radiologic, and pathologic study

Abstract: Background. Giant cell tumors (GCT) usually involve the epiphyses of long bones and only rarely involve the metaphysis or diaphysis without epiphyseal extension. Methods. This report presents the clinical and pathologic features of 14 patients with metaphyseal and diaphyseal GCT. Of these tumors, 10 were metaphyseal; 2, metadiaphyseal; and 2, diaphyseal. Results. The sites of involvement included the proximal tibia in six patients, distal radius in three, proximal fibula in one, distal fibula in one, distal ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 10 publications
1
35
1
1
Order By: Relevance
“…Of 1,682 cases of GCTB reported by the authors, only 14 (0.8%) were located in exclusively metaphyseal or diaphyseal regions. A notable finding of that study was the fact that the majority of patients with non-epiphyseal GCTB were <15 year-old (15). These unusual cases raised debate as to whether GCTB is capable of developing in the epiphysis (6,9) or in the metaphysis, with subsequent extension to the epiphysis following growth plate closure (16-18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 1,682 cases of GCTB reported by the authors, only 14 (0.8%) were located in exclusively metaphyseal or diaphyseal regions. A notable finding of that study was the fact that the majority of patients with non-epiphyseal GCTB were <15 year-old (15). These unusual cases raised debate as to whether GCTB is capable of developing in the epiphysis (6,9) or in the metaphysis, with subsequent extension to the epiphysis following growth plate closure (16-18).…”
Section: Discussionmentioning
confidence: 99%
“…Murphey et al (14) reported that in skeletally immature patients, GCTBs were located in metaphyseal rather than meta-epiphyseal bone, with an open epiphyseal plate acting as a barrier to tumor growth. Fain et al (15) reported non-epiphyseal GCTB of long bones. Of 1,682 cases of GCTB reported by the authors, only 14 (0.8%) were located in exclusively metaphyseal or diaphyseal regions.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to distinguish GCTs of the hand from other giant cell-rich lesions more common in those sites, including TB (7)(8)(9)(10)(17)(18)(19). The correct diagnosis depends on a high index of clinical suspicion, referral to mycobacterial laboratory tests, careful histologic examination of tissue samples and especially radiomorphologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…One reported patient had a lesion located in her second metatarsus, which, although not purely diaphyseal but rather metadiaphyseal, was very close to the epiphysis [18]. With two exceptions, all the cases reported by Uppin S. occurred in the expected location for a GCT, i.e., the epiphysis or metaepiphysis [17] Only one patient had a lesion in the diaphysis of her second metacarpus [17], a location that is considered as being very unusual for a GCT [10,18,19].…”
Section: Unusual Coexistence Of Giant Cell Tumor and Small Bone Tubermentioning
confidence: 99%
See 1 more Smart Citation